Direct pulmonary delivery of solubilized curcumin reduces severity of lethal pneumonia. Issue 12 (17th September 2019) - Zhang, Boya; Swamy, Samantha; Balijepalli, Sanjay; Panicker, Sreehari; Mooliyil, Jashitha; Sherman, Matthew A.; Parkkinen, Jaakko; Raghavendran, Krishnan; Suresh, Madathilparambil V.
Abstract : Acute respiratory distress syndrome (ARDS), the most severe form of acute lung injury, is associated with reduced lung compliance and hypoxemia. Curcumin exhibits potent anti‐inflammatory properties but has poor solubility and rapid plasma clearance. To overcome these physiochemical limitations and uncover the full therapeutic potential of curcumin in lung inflammation, in this study we utilized a novel water‐soluble curcumin formulation (CDC) and delivered it directly into the lungs of C57BL/6 mice inoculated with a lethal dose of Klebsiella pneumoniae ( KP ). Administration of CDC led to a significant reduction in mortality, in bacterial presence within blood and lungs, as well as in lung injury, inflammation, and oxidative stress. The expression of Klebsiella hemolysin gene; TNF‐α; IFN‐β; nucleotide‐binding domain, leucine‐rich‐containing family, pyrin domain‐containing‐3; hypoxia‐inducible factor 1/2α; and NF‐κB were also decreased following CDC treatment, suggesting modulation of the inflammasome complex and hypoxia signaling pathways as an underlying mechanism by which CDC reduces the severity of pneumonia. On a cellular level, CDC led to diminished cell death, improved viability, and protection of human lung epithelial cells in vitro . Overall, our studies demonstrate that CDC administration improves cell survival and reduces injury, inflammation, and mortality in a murine model of lethal gram‐negative pneumonia. CDC, therefore, has promising anti‐inflammatory potential in pneumonia and likely other inflammatory lung diseases, demonstrating the importance of optimizing the physicochemical properties of active natural products to optimize their clinical application.—Zhang, B., Swamy, S., Balijepalli, S., Panicker, S., Mooliyil, J., Sherman, M. A., Parkkinen, J., Raghavendran, K., Suresh, M. V. Direct pulmonary delivery of solubilized curcumin reduces severity of lethal pneumonia. FASEB J. 33, 13294–13309 (2019). www.fasebj.org